2020
DOI: 10.1371/journal.pone.0227232
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strontium and silicon substituted hydroxyapatite electrochemical coatings on bone ingrowth and osseointegration of selective laser sintered porous metal implants

Abstract: Additive manufactured, porous bone implants have the potential to improve osseointegration and reduce failure rates of orthopaedic devices. Substantially porous implants are increasingly used in a number of orthopaedic applications. HA plasma spraying-a line of sight process-cannot coat the inner surfaces of substantially porous structures, whereas electrochemical deposition of calcium phosphate can fully coat the inner surfaces of porous implants for improved bioactivity, but the osseous response of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 47 publications
0
32
0
1
Order By: Relevance
“…Moreover, Si-doped HA coating on the surface of Ti promoted migration and angiogenesis-related gene expression in human umbilical vein endothelial cells (HUVEC cell line). In another study, Mumith et al [40] assessed the effect of SiHA and strontium-substituted HA (SrHA) coatings on the Ti-6Al-4V implant on osseointegration in vivo using a sheep model. They proved that the implants electrochemically coated with SiHA and SrHA exhibited improved osseointegration compared to uncoated samples.…”
Section: Inorganic and Composite Coatingsmentioning
confidence: 99%
“…Moreover, Si-doped HA coating on the surface of Ti promoted migration and angiogenesis-related gene expression in human umbilical vein endothelial cells (HUVEC cell line). In another study, Mumith et al [40] assessed the effect of SiHA and strontium-substituted HA (SrHA) coatings on the Ti-6Al-4V implant on osseointegration in vivo using a sheep model. They proved that the implants electrochemically coated with SiHA and SrHA exhibited improved osseointegration compared to uncoated samples.…”
Section: Inorganic and Composite Coatingsmentioning
confidence: 99%
“…The mechanical benefit of bone formation in additively manufactured implants was demonstrated recently by an experiment that showed that the mechanical properties of porous implants improve by a factor of 2-7 when completely and homogenously filled with epoxy. However, several in vivo studies have shown that bone formation in implants is typically incomplete [8][9][10]. The performance of porous implants fabricated by additive manufacturing is a concern, as literature has reported a higher than expected failure rate for a porous acetabular component, and a Class 2 device recall of posteriorlateral lumbar cages due to preoperative and postoperative fracture [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…to produce functional coating in industry. Recently, the metal ion-substituted calcium phosphate coatings deposited by plasmaassisted techniques has been well-reviewed [43] and various cations, such as Sr, [44] Si, [45] Ce, [46] and Ta, [47] doped or co-doped coating via plasma-assisted methods for enhancing the biocompatibility of Ti have been reported.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Other plasma‐assisted methods including plasma spray, magnetron sputtering, pulsed laser deposition (PLD), and matrix‐assisted pulsed laser evaporation (MAPLE) are commonly used to produce functional coating in industry. Recently, the metal ion‐substituted calcium phosphate coatings deposited by plasma‐assisted techniques has been well‐reviewed [ 43 ] and various cations, such as Sr, [ 44 ] Si, [ 45 ] Ce, [ 46 ] and Ta, [ 47 ] doped or co‐doped coating via plasma‐assisted methods for enhancing the biocompatibility of Ti have been reported.…”
Section: Biofunctional Elements Incorporating Methodsmentioning
confidence: 99%
See 1 more Smart Citation